Sexual Behavior With Noncommercial Partners: A Concurrent Partnership Study Among Middle-Aged Female Sex Workers in China. Issue 4 (13th June 2019) - Guida, Jennifer; Hu, Liangyuan; Liu, Hongjie
Abstract : Female sex workers (FSWs) often engage in concurrent partnerships, meaning they have multiple sexual relationships at the same time. The objective of this study was to investigate sexual concurrency and its associations with condom use and syphilitic infections among FSWs over age 35. Respondent-driven sampling was used to recruit 1, 245 FSWs in Nanning, Hefei, and Qingdao, China. FSWs were asked to report whether they had concurrent partners in the past six months. Concurrency was defined as engagement in sex with commercial clients and (1) husbands and boyfriends (n = 167); (2) husbands only (n = 301); or (3) boyfriends only (n = 469). FSWs with only commercial clients were used as the comparison group (n = 308). Across all groups, the percentage of FSWs with prevalent and active syphilis ranged from 19.6% to 25.6% and 9.1% to 11.5%, respectively. Condom use was low with noncommercial sexual partners and was more likely to be used when FSWs' boyfriends had other partners. Three components of the theory of planned behavior were significantly associated with consistent condom use. Concurrent relationships may lead to increased transmission of syphilis at the workplace and family levels. Effective interventions should target concurrency with both commercial and noncommercial partners.